2021
DOI: 10.1002/lsm.23383
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Improve the Antimicrobial Efficacy of Photodynamic, Sonodynamic, and Sonophotodynamic Therapies

Abstract: Background and Objectives This work evaluated antimicrobial photodynamic therapy (PDT), sonodynamic therapy (SDT), and the association of both therapies (sonophotodynamic therapy [SPDT]), mediated by curcumin (Cur) against Staphylococcus aureus biofilm. Next, additional strategies for these treatments were assessed. Materials and Methods S. aureus biofilms received PDT, SDT, and SPDT, mediated by Cur (80 µM), LED light (450 nm), and 1 MHz ultrasound. The same treatments were also performed adding a strategy: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 24 publications
(37 reference statements)
1
31
0
Order By: Relevance
“…In their ex vivo study, chitosan nanoparticles indocyanine green-mediated aPSDT decreased the polymicrobial periopathogenic biofilms on surfaces of the titanium dental implants to 90.5%. The inactivation of Candida albicans biofilms using combined aPDT/aSDT in oropharyngeal candidiasis was highlighted by Alves et al [ 18 ]. Xu et al [ 37 ] reported that synergistic aPDT and aSDT improved the inhibition rate of antibiotic-resistant bacteria in infectious diseases compared with either the aPDT or aSDT alone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In their ex vivo study, chitosan nanoparticles indocyanine green-mediated aPSDT decreased the polymicrobial periopathogenic biofilms on surfaces of the titanium dental implants to 90.5%. The inactivation of Candida albicans biofilms using combined aPDT/aSDT in oropharyngeal candidiasis was highlighted by Alves et al [ 18 ]. Xu et al [ 37 ] reported that synergistic aPDT and aSDT improved the inhibition rate of antibiotic-resistant bacteria in infectious diseases compared with either the aPDT or aSDT alone.…”
Section: Discussionmentioning
confidence: 99%
“…aSDT, as a novel ultrasound-driven treatment has been found to be very effective in killing microorganisms due to its strong penetrating power through a sonochemical process [ 17 ]. Several recent reports have mentioned satisfactory results with aSDT in inhibiting microorganisms due to its non-invasive nature [ 17 , 18 , 25 ]. The main advantage of aSDT over aPDT is the increased penetration of ultrasound irradiation to the target site compared to light [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… Sonosensitizers Purpose Mechanisms Ref. HMME Medical Increase in intracellular ROS [52] PPPC Medical Cell membrane damage [53] Fe@UCNP- HMME Medical Cell membrane damage [65] UCNP@SiO 2 -RB/HMME Medical Cell membrane damage [76] Pd @ Pt-T790 Medical Increase in intracellular ROS [29] Cur Food DNA damage a [61] Cur Medical DNA damage a [60] Cur Medical Downregulation in virulence genes [68] Cur Medical Cell membrane damage [67] Hypocrellin B Medical Cell membrane damage DNA damage a [62] Nano-emodin Medical Downregulation in virulence genes [63] Propyl gallate Food Lipid peroxidation [69] Amphotericin B Medical Increase in intracellular ROS [70] MLP18 Medical Cell membrane damage Increase in intracellular ROS Drug delivery [38] TiO 2 Medical Oxidative stress response [71] Non-woven TiO 2 Environment Lipid peroxidation …”
Section: Cellular Oxidation ─ Antibacterial Mechanism Of Rosmentioning
confidence: 99%